Academics of the Early Primary Grades: Investigating the Alignment of Instructional Practices from Pre-K to Third Grade. Issue 7 (3rd October 2022) - Justice, Laura M.; Jiang, Hui; Purtell, Kelly M.; Lin, Tzu-Jung; Ansari, Arya
ABSTRACT: Research Findings : The present study examined the extent to which instructional practices, including curriculum, in pre-K through third grade are vertically aligned. Attention was directed to teachers' grouping practices, academic content, and pedagogical methods given their importance for students' learning. Variable- and person-centered analyses examined these practices for a sample of 1, 095 students in 179 pre-K through third-grade classrooms. A comparison of practices indicated that pre-K practices were significantly mis-aligned from those used in kindergarten through third grade, whereas kindergarten practices were well aligned with practices used in the older grades. Examination of profiles of classroom practices showed there to be four profiles, one of which was considered as "academic-light group work, " which was dominated by pre-K and kindergarten classrooms. Practice or policy : Overall, this study found that instructional practices in pre-K were starkly different from those in kindergarten through third grade, and that kindergarten appears to be highly academic for about two-thirds of classrooms. This work underscores the importance of practices and policies that promote alignment from pre-K into the primary grades and how it might be enhanced.